2020
DOI: 10.1001/jamainternmed.2020.4616
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating the Association of Clinical Characteristics With Neutralizing Antibody Levels in Patients Who Have Recovered From Mild COVID-19 in Shanghai, China

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) threatens global public health. The association between clinical characteristics of the virus and neutralizing antibodies (NAbs) against this virus have not been well studied. OBJECTIVE To examine the association between clinical characteristics and levels of NAbs in patients who recovered from COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
193
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(235 citation statements)
references
References 18 publications
(33 reference statements)
36
193
3
3
Order By: Relevance
“…It was reported that stronger antibody response was associated with delayed viral clearance and increased disease severity in patients of COVID-19 30 . We also reported that NAb titers were higher in elderly patients of COVID-19, who tend to have worse outcomes, while a few patients recovered without generating detectable NAbs 18 Figure 9). We found that amino acid substitutions F342L and E516A on RBD allowed the virus escape from the neutralization by 7F3 without reducing binding affinity to antibody.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…It was reported that stronger antibody response was associated with delayed viral clearance and increased disease severity in patients of COVID-19 30 . We also reported that NAb titers were higher in elderly patients of COVID-19, who tend to have worse outcomes, while a few patients recovered without generating detectable NAbs 18 Figure 9). We found that amino acid substitutions F342L and E516A on RBD allowed the virus escape from the neutralization by 7F3 without reducing binding affinity to antibody.…”
Section: Discussionmentioning
confidence: 57%
“…17 [13][14][15][16][17][18][19][20][21][22][23] days, P < 0.0001, Figure 1I and 1J). These results indicated that ADE is more likely to develop in elderly patients with severe and critical condition, longer hospital stays and disease duration, suggesting a possible association of ADE with disease severity in COVID-19 patients.…”
Section: Ade Is More Likely To Develop In Elderly Patients With Severmentioning
confidence: 99%
“…In both humans and animals, such cross-reactivity was suspected to be due to non-neutralizing anti-S antibody again likely relating to a conserved region [33]. Crossneutralization was however uncommon, but conceivably there could be other reasons for any such non-specificity [34][35][36]. Among humans, S-specific antibody dominates and may correlate better with neutralization [34,35,37].…”
Section: Provisional Acceptance Of What Constitutes Immunitymentioning
confidence: 99%
“…Crossneutralization was however uncommon, but conceivably there could be other reasons for any such non-specificity [34][35][36]. Among humans, S-specific antibody dominates and may correlate better with neutralization [34,35,37]. Furthermore, the correlation between antibodies for different antigens (e.g., S and N proteins) may not be as initially conceived [35,38].…”
Section: Provisional Acceptance Of What Constitutes Immunitymentioning
confidence: 99%
See 1 more Smart Citation